2020
DOI: 10.1029/2019jc015848
|View full text |Cite
|
Sign up to set email alerts
|

Bistability of the Filchner‐Ronne Ice Shelf Cavity Circulation and Basal Melt

Abstract: Circulation and water mass transformation within the Filchner-Ronne Ice Shelf (FRIS) cavity create precursors to Antarctic bottom water, which closes the global overturning circulation. This water mass transformation is contingent upon a relative low rate of FRIS basal melt, currently around 100-200 Gt/yr. Previous studies have indicated that Antarctic climate changes may induce intrusions of warm modified Warm Deep Water (mWDW) and an order-of-magnitude increase in basal melt, and signatures of mWDW have r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
27
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 84 publications
6
27
3
Order By: Relevance
“…Thermocline heaving alone does not cause an increased inflow of warm water since the pathway along the deep Filchner Trough is blocked by the presence of DSW masses. In agreement with Hellmer et al (2017) and Hazel and Stewart (2020), we find that the density structure in Filchner Trough is crucial for determining the water exchange across its sill. The blocking effect decreases when the DSW becomes fresher and ceases if the DSW becomes lighter than the WDW.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Thermocline heaving alone does not cause an increased inflow of warm water since the pathway along the deep Filchner Trough is blocked by the presence of DSW masses. In agreement with Hellmer et al (2017) and Hazel and Stewart (2020), we find that the density structure in Filchner Trough is crucial for determining the water exchange across its sill. The blocking effect decreases when the DSW becomes fresher and ceases if the DSW becomes lighter than the WDW.…”
Section: Resultssupporting
confidence: 92%
“…A positive meltwater feedback, where enhanced freshwater input from FRIS basal melt reduces the shelf salinity and further strengthens the warm inflow, may contribute to drive the system past a tipping point (Hellmer et al, 2017). These results are supported by a regional model study (Hazel & Stewart, 2020), which also suggests that offshore katabatic winds may affect the FRIS cavity circulation through modulation of sea ice formation and the freshwater flux. The uncertainties in the high‐melt model studies (BRIOS and RAnGO) and the CMIP5 scenarios are pronounced (see Figure 1b), and the oceanic processes controlling the warm inflows are strongly related to the projected atmospheric forcing (Timmermann & Hellmer, 2013).…”
Section: Introductionsupporting
confidence: 74%
“…Using an ice-ocean model forced with a climate change projection, Warm Deep Water (WDW) from offshore was simulated to enter the cavity through the Filchner Trough, dramatically increasing basal melt rates. A similar circulation change has been triggered in other ocean models by manually varying the cavity salinity or atmospheric forcing 11 , 12 . However, it remains unclear how easily this circulation change could occur in reality, and over what timescales.…”
Section: Introductionmentioning
confidence: 79%
“…Our results suggest that ice‐shelf/ocean modelers should carefully consider their choice of boundary conditions when running limited area models of the region. In some idealized cases, it has been past practice to use climatological boundary conditions for regional modeling studies (e.g., Hazel & Stewart, 2020; Naughten et al., 2019) but consistency between the boundary conditions and the local forcing is important for realistic representation of inter‐annual variability in re‐analysis focused studies (e.g., Hausmann et al., 2020). More generally, Figures 1a–1f show differences in the observed and simulated temperature and salinity structure of the ASC across different products/time periods.…”
Section: Summary and Further Workmentioning
confidence: 99%
“…(2019) showed that offshore polynyas in the Weddell Sea can increase the transport of WDW across the shelf through density changes above the shelf break. Hazel and Stewart (2020) suggest that decreasing the meridional winds by 50% can switch FRIS from a cold to warm state. In the broader context, several modeling studies in the Amundsen Sea have reported changes in far‐field forcing as a contributing factor to Circumpolar Deep Water crossing the shelf (Donat‐Magnin et al., 2017; Nakayama et al., 2018; Spence et al., 2017; Webb et al., 2019).…”
Section: Introductionmentioning
confidence: 99%